PENERAPAN ATURAN DELIK PENIPUAN DALAM KASUS PENERBITAN BILYET GIRO KOSONG - Siagian, Borris Ficthe (Justitia et Pax, 2019)
Bilyet giro is a payment instrument that use for a non cash payment. It’s  a payment order for the bank to transfer a money form drawer‘s giro account to receiver’s giro account. Bilyet giro users know term the empty of bilyet giro, that is a bilyet giro that has been rejected by bank so bank don’t take order from bilyet giro. Someone that draw it, also known as defaulting party in civil law. Society development make the empty of bilyet giro become a criminal acts of fraud, through KUHP article 378. This research gaols is to find out, is it possible for that case that  related to a civil law can be implement with a criminal acts of fraud. Analysis method in this research used a qualitive method that analyzing obtained data and conclude them with deductive way that relate to how to implement a criminal acts of fraud this case. This research result is the acts of fraud can be implement to this case when in that case include some lie, that’s one of the element of KUHP article 378. This Implementation is to punish someone that uses the empty of bilyet giro as a tool to cheat other.